The life-course approach to vaccination: Harnessing the benefits of vaccination throughout life. Issue 44 (16th October 2019) - Tate, Jody; Aguado, Teresa; Belie, Jan De; Holt, Daphne; Karafillakis, Emilie; Larson, Heidi J.; Nye, Sam; Salisbury, David; Votta, Mariano; Wait, Suzanne
Abstract: Vaccination beyond childhood brings significant benefits at the individual, community and socio-economic levels. Despite this, immunisation programmes often fail to deliver the vaccines which could protect those at risk of vaccine-preventable diseases. In this commentary, we argue that the benefits of vaccination beyond childhood must be more widely understood and furthermore, that action must be taken by policymakers, healthcare professionals and patient and civil society organisations to ensure that the benefits of vaccination are fully realised. We outline five areas where change is needed to ensure vaccination across the life-course becomes truly embedded in national immunisation programmes. This includes investing in robust data collection and analysis; ensuring coordinated, multidisciplinary leadership from the top; engaging healthcare professionals; changing public perceptions of vaccination; and integrating vaccination into schools and workplaces.